2009
DOI: 10.1007/s00221-008-1690-4
|View full text |Cite
|
Sign up to set email alerts
|

Retinal projections to the accessory optic system in pigmented and albino ferrets (Mustela putorius furo)

Abstract: We investigated if a reduced specificity of the retinal projection to the accessory optic system might be responsible for the loss of direction selectivity in the nucleus of the optic tract and dorsal terminal nucleus (NOT-DTN) and, in consequence of this, the optokinetic deficits in albino ferrets. Under electrophysiological control we performed dual tracer injections into the NOT-DTN and the medial terminal nucleus (MTN). Retrogradely labelled ganglion cells were found in the visual streak, the dorsal, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…nasotemporal, preferred direction in the ipsilateral section of their receptive fields leading to an inverted monocular horizontal optokinetic nystagmus from that section of their visual field (Collewijn et al ., ; Winterson & Collewijn, ), a finding that was not directly supported by anatomical evidence for an abnormally crossed projection of DSGCs from the temporal retina (Klooster et al ., ). By retrograde labeling, we found more retinal ganglion cells projecting simultaneously to the NOT–DTN and MTN in albino ferrets than pigmented ferrets (Distler et al ., ) but, again, the effect seemed too small to explain the complete loss of direction selectivity in the NOT–DTN. This idea is also refuted by our finding of a fixed angle of about 130° between two clusters of preferred directions in the MTN‐projecting DSGCs in pigmented as well as albinotic rats, which is very similar to the published difference angles in rabbit (Oyster, ) and mouse (Dhande et al ., ).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…nasotemporal, preferred direction in the ipsilateral section of their receptive fields leading to an inverted monocular horizontal optokinetic nystagmus from that section of their visual field (Collewijn et al ., ; Winterson & Collewijn, ), a finding that was not directly supported by anatomical evidence for an abnormally crossed projection of DSGCs from the temporal retina (Klooster et al ., ). By retrograde labeling, we found more retinal ganglion cells projecting simultaneously to the NOT–DTN and MTN in albino ferrets than pigmented ferrets (Distler et al ., ) but, again, the effect seemed too small to explain the complete loss of direction selectivity in the NOT–DTN. This idea is also refuted by our finding of a fixed angle of about 130° between two clusters of preferred directions in the MTN‐projecting DSGCs in pigmented as well as albinotic rats, which is very similar to the published difference angles in rabbit (Oyster, ) and mouse (Dhande et al ., ).…”
Section: Discussionmentioning
confidence: 96%
“…(). Together, these findings falsify one of our hypotheses put forward to explain the loss of direction selectivity in the AOS of albinotic rats, namely that a deterioration of direction selectivity in the retina could cause this loss and thus the optokinetic deficits observed in some albino mammals (Distler et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…However, the evidence for ipsilateral projections from the retina to NOT is debated. While ipsilateral projections are found in pigmented ferrets, 22 older studies reported ipsilateral projections seem to be weak or absent in rabbits and mice. 23 , 24 More recent studies in mice using genetic fluorescent tracers, however, show the presence of ipsilateral retinal axons in the NOT 25 , 26 and give new life to the hypothesis that the miswiring of retinal inputs to the NOT underlies optokinetic problems in albinos.…”
mentioning
confidence: 87%